2008
DOI: 10.1083/jcb.200803071
|View full text |Cite
|
Sign up to set email alerts
|

Lis1 and Ndel1 influence the timing of nuclear envelope breakdown in neural stem cells

Abstract: Lis1 and Ndel1 are essential for animal development. They interact directly with one another and with cytoplasmic dynein. The developing brain is especially sensitive to reduced Lis1 or Ndel1 levels, as both proteins influence spindle orientation, neural cell fate decisions, and neuronal migration. We report here that Lis1 and Ndel1 reduction in a mitotic cell line impairs prophase nuclear envelope (NE) invagination (PNEI). This dynein-dependent process facilitates NE breakdown (NEBD) and occurs before the est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(119 citation statements)
references
References 31 publications
6
113
0
Order By: Relevance
“…It has been reported that p150 Glued colocalized with Lis1 at the NE in nocodazoletreated cells (12). Here, we further show that p150 Glued accumulated at the NE in prophase cells under normal growth conditions (Fig.…”
Section: Accumulation Of P150 Glued At the Ne In Prophase Is Positivelysupporting
confidence: 84%
See 1 more Smart Citation
“…It has been reported that p150 Glued colocalized with Lis1 at the NE in nocodazoletreated cells (12). Here, we further show that p150 Glued accumulated at the NE in prophase cells under normal growth conditions (Fig.…”
Section: Accumulation Of P150 Glued At the Ne In Prophase Is Positivelysupporting
confidence: 84%
“…Immunostaining was performed as previously described (12). Briefly, HeLa and U2OS cells were plated onto 12-mm glass coverslips in sixwell plates.…”
Section: Methodsmentioning
confidence: 99%
“…Emerging evidence suggests that LIS1 and NDEL1 contribute to many dynein-related activities in neurons; reduced expression of LIS1 and NDEL1 in neural precursor cells increased average centrosome-nucleus spacing, and LIS1 interference caused inhibition of centrosomal migration (15) and somal translocation (16). Reduction of LIS1 and NDEL1 in a mitotic cell line impaired prophase nuclear envelope invagination (17). However, although many observations suggest that LIS1 and NDEL1 regulate dynein at the cellular level, the underlying mechanism remains elusive.…”
mentioning
confidence: 99%
“…NDEL1 is differentially phosphorylated by CDK1 (Yan et al, 2003) and CDK5 (Niethammer et al, 2000). Interestingly, NDEL1 double phosphorylation by CDK1 and CDK5 reduced the amount of NDEL1 and LIS1 that coimmunoprecipitated with dynein, suggesting that phosphorylation not only strengthens NDEL1 binding to LIS1 but promotes the release of LIS1-pNDEL1 complexes from dynein (Hebbar et al, 2008). In contrast, phosphorylation by either kinase alone was insufficient to reduce dynein binding.…”
Section: Novel Role Of Mitotic Kinase In Neuronal Migrationmentioning
confidence: 98%